The integrated nervous system :a systematic diagnostic case-based approach - Hendelman, Walter (CRC, 2018)
This innovative textbook is modelled on problem-based learning. It bridges the gap between academic neuroanatomy and clinical neurology and effectively takes the reader from the classroom to the clinic, so that learning can be applied in practice.